2014 Annual IEEE India Conference (INDICON) 2014
DOI: 10.1109/indicon.2014.7030462
|View full text |Cite
|
Sign up to set email alerts
|

Stability and variability enhancement of 9T SRAM cell for subthreshold operation

Abstract: This article presents a new way for designing a more reliable and variability resilient 9T SRAM cell which is based on DTMOS (dynamic threshold MOS) and CCBB (cell content body bias) technique under subthreshold operation. Critical design metrics of SRAM cells are estimated at subthreshold region and compared with that of conventional 9T SRAM cell. The proposed 9T SRAM cell shows 41.8% (9.5%) lower read access time (write access time) compared to conventional 9T SRAM cell. It also exhibits robustness by achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Karthika and SivaMangai (2016) showed that 9T SRAM array with bit interleaving architecture consumes low power with good stability compared to the shared wordline architecture using 6T SRAM cell. Anand et al (2014) proposed two different optimization techniques for more reliable and stable 9T SRAM. By using these two techniques namely, Cell Content Body Bias (CCBB) and Dynamic threshold MOS (DTMOS) for sub-threshold region, it is found to have better RSNM at 0.35V, 41.8% bottom read access time, narrower spread in write access and read access time as 8 and 53.01% respectively over conventional 9T cell.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karthika and SivaMangai (2016) showed that 9T SRAM array with bit interleaving architecture consumes low power with good stability compared to the shared wordline architecture using 6T SRAM cell. Anand et al (2014) proposed two different optimization techniques for more reliable and stable 9T SRAM. By using these two techniques namely, Cell Content Body Bias (CCBB) and Dynamic threshold MOS (DTMOS) for sub-threshold region, it is found to have better RSNM at 0.35V, 41.8% bottom read access time, narrower spread in write access and read access time as 8 and 53.01% respectively over conventional 9T cell.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1. The 6T cell has a high power consumption [1, 2]. According to the literature, the most effective method for reducing power consumption is cell design in sub‐threshold region on lower VDDs [3].…”
Section: Introductionmentioning
confidence: 99%